Better Sentence Structure Through Diagramming - Dressel, Mark and Carnevale, Greg. (Instructional Fair, Inc., 1995)
Diagramming enables students to gain a better understanding of sentence structure and parts of speech. Each lesson describes the specific structure under study, gives examples, and provides sentences for diagramming practive. Students are then challenged to generate their own sentences to fit the models. Even teachers unfamiliar with the diagramming process will find this step-by-step format easy to follow and use to instruct students.
Keywords: English Practice